A Character Education Framework Grounded in Exemplary Leadership: Insights and Applications - Mubarok, Muhammad Khusni; Syakur, Abd.; Fahmi, Moh. Farih; Prasetya, Rizki (Universitas Islam Negeri Raden Intan Lampung, 2024)
Character education is a fundamental aspect of human development, as it shapes individuals into ethical and responsible members of society. This study explores the effectiveness of exemplary leadership as a method for character education through a Systematic Literature Review (SLR). The findings reveal that exemplary teaching methods play a pivotal role in fostering holistic character development by integrating cognitive, affective, and psychomotor domains. These methods enable educators to act as role models, guiding students to internalize and practice ethical values in their daily lives. Despite its potential, the study identifies gaps in the systematic application of exemplary leadership within educational practices, particularly in teacher training programs. Addressing these challenges requires collaborative efforts among educators, policymakers, and communities. This research underscores the transformative potential of exemplary leadership in addressing moral challenges and promoting sustainable character education across diverse educational contexts. The findings contribute valuable insights to the field of character education, offering a robust framework for implementation and policy development.